2015
DOI: 10.5812/aapm.25036
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Education and Decreasing Preoperative Anxiety Among Children Aged 8 - 10 Years Old and Their Mothers

Abstract: Background:Preoperative anxiety is associated with adverse clinical, behavioral, and psychological outcomes. Various effective interventions targeting preoperative anxiety in children exist.Objectives:The aim of this study was to evaluate the educational intervention by residents on children and maternal anxiety and their satisfaction from anxiety management.Patients and Methods:After obtaining the institutional ethics committee approval and written informed parental consent, 36 ASA-I, II children (age range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
2
22
0
6
Order By: Relevance
“…Moreover, story coloring booklet for children during the waiting period for surgery distracted them from the stressful hospital situation (Tanaka et al, 2011). It is documented that lack of knowledge of what will happen is the main cause of children anxiety before surgery (Copanitsanou & Valkeapää, 2014); Tabrizi et al, 2015). In the same stream, the current study intervention might increase knowledge of children in the intervention group about surgery.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, story coloring booklet for children during the waiting period for surgery distracted them from the stressful hospital situation (Tanaka et al, 2011). It is documented that lack of knowledge of what will happen is the main cause of children anxiety before surgery (Copanitsanou & Valkeapää, 2014); Tabrizi et al, 2015). In the same stream, the current study intervention might increase knowledge of children in the intervention group about surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Chorney and Kain (2010) suggested that family contribution enhances communication, coordination, and unification of care provided which will positively impact children outcomes. Studies found that children who were prepared on the day before surgery reported a significantly decrease in the anxiety levels as compared with children who were not prepared (Kathalae, 2007, Vaezzadeh et al, 2011, Tabrizi et al, 2015. Inconsistent results were reported in former study as no difference in the anxiety levels of children were seen when children in the intervention groups practiced storytelling and coloring activities before surgery (Al-Yateem et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Again, the pain education booklet focused on pain management strategies rather than explaining the neuroscience of pain. More recently, Tabrizi and colleagues [50] investigated the use of an anesthesia education booklet to alleviate preoperative anxiety in children ages 8–10 and their parents. Whilst parents and children receiving the education intervention reported reduced preoperative anxiety, similar reductions were seen in a control group receiving routine preoperative preparation without education.…”
Section: Overview Of Pain Neuroscience Educationmentioning
confidence: 99%